A semi-industrial AnMBR plant for urban wastewater treatment at ambient temperature: Analysis of the filtration process, energy balance and quantification of GHG emissions. Issue 2 (April 2023) - Jiménez-Benítez, A.; Ruiz-Martínez, A.; Robles, Á.; Serralta, J.; Ribes, J.; Rogalla, F.; Seco, A.; Ferrer, J.
Abstract: A semi-industrial scale AnMBR urban wastewater treatment plant was operated for 580 days at ambient temperature (ranging from 10 to 30 ○ C) to assess its long-term filtration performance, energy balance and GHG emissions. The applied 20ºC-standardized transmembrane flux (J20 ) was varied between 15 and 25 LMH and the specific gas demand per m 2 of membrane (SGDm ) was modified between 0.10 and 0.40 Nm 3 ·m −2 ·h −1 (corresponding to a specific gas demand per permeate volume (SGDP ) between 10 and 20 Nm 3 ·m −3 ). The filtration strategy allowed successful long-term operations without any chemical cleaning requirements and little fouling for 233 days. The plant operated as a net energy producer for more than 50 % of the experimental period, with an average net energy demand of − 0.169 ± 0.341, − 0.190 ± 0.376 and − 0.205 ± 0.447 kWh·m −3, considering 0 %, 50 % and 70 % of dissolved methane recovery, respectively. Finally, demethanization of AnMBR effluent is needed to achieve an environmentally sustainable operation of the technology. Therefore, the combination of AnMBR with degassing membranes appears as a suitable alternative to conventional wastewater treatment. Graphical Abstract: ga1 Highlights: Urban wastewater can be treated by AnMBR technology at low ambient temperatures. The process was net energy producer (energy surplus of 0.169 kWh·m −3 in average). Competitive J20 were reached (15–20 LMH) with low SGD values (0.1–0.4 Nm 3 ·m −2 ·h −1 ). Energy consumption in reactor mixing and membrane scouring was < 0.19 kWh·m −3 . GHG emissions below 0.2 kgCO2 ·m −3 when 70 % of dissolved methane was recovered.